Pengaruh Konsentrasi Etanol dan Waktu Ekstraksi menggunakan Metode Microwave Assisted Extraction (MAE) terhadap Aktivitas Antioksidan Ekstrak Kulit Buah Kakao - Puspitaningtyas, Diana; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
This research was conducted to determine effect of ethanol concentration and extraction time on antioxidant activity of cocoa pod husk extract and to obtain ethanol concentration and extraction time using Microwave Assisted Extraction (MAE) that can produce extract with the highest antioxidant capacity. The experimental design used in this research was a factorial randomized block design, which consisted of two factors. The first factor was the concentration of ethanol which consisted of 3 level that namely ethanol 75%, 85% and 95%. The second factor was the time of extraction which consisted of 4 level namely 5, 10, 15, and 20 minutes. The data were analyzed by analysis of variance and continued with Tukey test. The results showed that the concentration and extraction time had a very significant effect on yield, total phenolic, total flavonoid and antioxidant capacity of cocoa pod husk extract. Interactions between treatments had a very significant effect on total phenolic and total flavonoid. Interaction on antioxidant capacity had a significant effect, but did not significantly effect to the yield of cocoa pod husk extract. The best treatment showed that extraction by ethanol 95% for 15 minutes using MAE which the characteristic yield was 11.85±0.84% total phenol was 149.36±0.92 mg GAE/g extract, total flavonoid was 91.03±2.31 mgQE/g extract, antioxidant capacity was 136.69±0.19 mg GAEAC/g extract. Keyword : Ethanol concentration, time extraction, antioxidants, cocoa pod husk.